Fifth International Conference on Quality Software (QSIC'05)
DOI: 10.1109/qsic.2005.3
|View full text |Cite
|
Sign up to set email alerts
|

A Metamorphic Approach to Integration Testing of Context-Sensitive Middleware-Based Applications

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Experimental results of the evaluation of the metamorphic relations using manual mutation testing were reported. In [9], Chan et al presented a metamorphic approach for integration testing in context-sensitive middleware-based applications. The authors identified functional relations that associate different execution sequences of a test case.…”
Section: Related Workmentioning
confidence: 99%
“…Experimental results of the evaluation of the metamorphic relations using manual mutation testing were reported. In [9], Chan et al presented a metamorphic approach for integration testing in context-sensitive middleware-based applications. The authors identified functional relations that associate different execution sequences of a test case.…”
Section: Related Workmentioning
confidence: 99%
“…Tse et al [2004] and Chan et al [2006] explored new ways to verify test results based on metamorphic relationships derived from context-aware applications. Lu et al [2006] proposed to generalize the concept of "data definition" to "data update" to model that contexts can be sensed (updated) directly by the pervasive environment rather than just by program statements.…”
Section: Pervasive Computing and Context Awarenessmentioning
confidence: 99%
“…Noting that the output of a test case for pervasive applications can be too transient to record, Chan et al [6] advocated the use of metamorphic relations among different contexts to address the test oracle problem. Observing that layered architecture disseminated the complete application logic of pervasive software into multiple tiers, Lu et al [18] [19] proposed to assemble context-aware entities (including adaptation rules and context management components such as CIR services) into a traditional control-flow-graph model and developed new coverage-based testing criteria to dynamically verify the definition and use of variables in pervasive software.…”
Section: Related Workmentioning
confidence: 99%